Mampukah Komisaris Independen Memoderasi Pengaruh Kinerja Keuangan Terhadap Tax Avoidance? - Sevi Lestya Dewi; Rachmawati Meita Oktaviani (Jurnal Akademi Akuntansi, 2022)
The purpose of this study was to determine the effect of capital intensity and leverage on tax avoidance with independent commissioner as moderating variable. The population in this study is the manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The method of determining the sample used purposive sampling and obtained 75 observation. The method of analysis in this study used panel data moderated regression analysis (MRA). The result of the analysis showed that the capital intensity has a positif effect on tax avoidance. The higher capital intensity, the lower the practice of tax avoidance. Leverage has no effect on tax avoidance. The higher laverage on company will not have an impact on tax avoidance. The proportion of independent commissioner can weaken the moderated effect of capital intensity on tax avoidance. The higher the independent commissioner will monitoring the capital intensity ratio on tax avoidance. Independent commissioner does not moderated the effect of leverage on tax avoidance. The proportion of independent commissioner has no impact on leverage decisions on tax avoidance.